Knowledge and Attitude of Farmers Towards Agroforestry Practices in North Kashmir - a Case Study - Banyal, R.; Masoodi, N. A.; Masoodi, T. H.; Sharma, L. K.; Gangoo, S. A. (Indian Forester, 2011)
The present investigation sought to explore the knowledge and attitude of farmers towards agroforestry practices especially in North Kashmir of Western Himalayas. The informations gathered through the systematic survey by filling the testified questionnaire. A sample of 100 homesteads (41%) from the village was selected through random sampling technique. The responses were analyzed by using Frequency and Percentage Method (FMP). The results revealed that the inhabitants of study area are not well aware about the key points tested under knowledge of farmers about tree farming. On an average of 15 key points (studied), the majority of respondents fall in ’not at all’ (38.23%), followed by ’moderate extent’ (31.29%), ’large extent’ (26.27%) and ’little extent’ (19.08%) categories, respectively. Time and stage of tree felling ranked first in all the responses and VAM inoculation at the bottom. The data on attitude of farmers towards agroforestry with its benefits reveal that 58.20 per cent respondents fall in the ’agree category’ followed by ’strongly agree’ (21.00%) and ’neutral’ (20.60%). It is observed that farmers are also reluctant to go for only agroforestry practices due to smaller land holdings. The response regarding agroforestry helps in making the farmers self-reliant ranked first in order. The present study revealed that subsidy is the only response holding the key as motivational factor for adoption of agroforestry practices.